2013
DOI: 10.1080/1081602x.2012.731016
|View full text |Cite
|
Sign up to set email alerts
|

Differences in intergenerational fertility associations by sex and race in Saba, Dutch Caribbean, 1876–2004

Abstract: This study examines the intergenerational transmission of fertility behavior in Saba, Dutch Caribbean from 1876 to 2004 using reconstituted genealogies. Pearson product-moment correlation coefficients of several fertility measures and event-history models of age at first birth are used to explore relationships between the fertility of mothers and their children. The strength of intergenerational fertility ties varies by race and gender. Individuals that are better positioned to realize their fertility preferen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 43 publications
0
13
0
Order By: Relevance
“…Most of the literature has focused on women only, but studies including both sexes or the male partner’s characteristics have shown that the number of siblings plays a role for both sexes (Booth and Kee 2009 ; Jennings and Leslie 2012 ; Nisén et al 2013 ; Rotering 2017 ). Across the twentieth century, the intergenerational correlation was higher for women than for men.…”
Section: Previous Findings About the Parent-child Fertility Relationsmentioning
confidence: 99%
“…Most of the literature has focused on women only, but studies including both sexes or the male partner’s characteristics have shown that the number of siblings plays a role for both sexes (Booth and Kee 2009 ; Jennings and Leslie 2012 ; Nisén et al 2013 ; Rotering 2017 ). Across the twentieth century, the intergenerational correlation was higher for women than for men.…”
Section: Previous Findings About the Parent-child Fertility Relationsmentioning
confidence: 99%
“…This reflects selection processes that cause the continuing relationship, because parents and children are exposed to similar opportunity structures. Results on this mechanism are contradictory: Although many studies show that socialisation is more important than the transmission of socioeconomic status (Kolk 2014), various studies consider the transmission of socioeconomic status as an explanation as well (Barber 2001;Jennings and Leslie 2012;Rijken and Liefbroer 2009). Some of them find that the transmission of socioeconomic status mediates the relationship between mothers' and daughters' fertility, while others report remaining intergenerational transmission net of socioeconomic status (Booth and Kee 2009;Dahlberg 2013;Murphy and Knudsen 2002;Rijken and Liefbroer 2009).…”
Section: Potential Mechanisms: Theory and Empirical Researchmentioning
confidence: 99%
“…The study of intergenerational transmission in the research of the connections between the values of the family of origin and the attitudes towards family life has a history of a hundred years (PEARSON et al 1899), the connection between the fertility of parents and their children, and the similarity in the planned number of children have been proved by several researches (JENNINGS & LESLIE 2013;BRAS et al 2013;RIJKEN & LIEFBROER 2009;BERNARDI 2016). Empirical studies that focus on the effect of the family of origin on fertility found positive correlation between the number of children of successive generations in the same family as well as the age of mothers and daughters entering into parenthood (MANLOVE 1997;BARBER 2000).…”
Section: Introductionmentioning
confidence: 99%